PATHOGENESIS OF HEMORRHAGIC DUE TO DENGUE VIRUS - Suseno, Arief; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2015)
Dengue is a viral disease that is mediated by a mosquito, which causes morbidity and mortality. Viruses can increase vascular permeability which can lead to hemorrhagic diathesis or disseminated intravascular coagulation (DIC) known as dengue hemorrhagic fever (DHF). In Indonesia, dengue hemorrhagic fever (DHF) are caused by dengue virus infection which was found to be endemic accompanied by an explosion of extraordinary events that appear at various specified period. The diagnosis of dengue is determined based on the criteria of the World Health Organization (WHO, 1999), which are sudden high fever accompanied by a marked tendency to hemorrhage positive tourniquet test, petechiae, ecchymosis, purpura, mucosal hemorrhagic, hematemesis or melena and thrombocytopenia. The problem that still exists today is the mechanism of thrombocytopenia in patients with varying degrees of dengue involving levels of vWF (von Willebrand factor) and prostaglandin I2 (PGI2) can not be explained. The mechanism of hemorrhagic in dengue virus infections acquired as a result of thrombocytopenia, platelet disfunction decreased coagulation factors, vasculopathy with endothelial injury and disseminated intravascular coagulation (DIC).